Colchicine in Coronary Artery Disease: An Old Acquaintance in New Attire? - Giannopoulos, Georgios; Angelidis, Christos; Papoutsidakis, Nikolaos; Panagopoulou, Vasiliki; W. Cleman, Michael; Lekakis, John; Deftereos, Spyridon (Current Medicinal Chemistry, 2015)
Colchicine has recently gained considerable attention in the field of cardiovascular research, after a number of studies showed that it may be of use in several settings of cardiovascular disease, including chronic coronary artery disease and following stent implantation. Its unique anti-inflammatory mechanism of action makes it safe to use in patients with cardiovascular disease, unlike most – if not all – currently available antiinflammatory agents. While its prophylactic and therapeutic value is well-established in certain conditions involving an acute inflammatory response, e.g. pericarditis, in other conditions, including coronary artery disease and heart failure, which are associated with a chronic low-grade inflammatory state, the evidence regarding its potential use remains sparse. In this concise review, we present key features of this drug and the rationale for colchicine therapy, in the context of acute and chronic coronary artery disease, as well as in ischemic heart failure and critically examine the evidence concerning a possible future role of colchicine treatment in these conditions.
Keywords: pharmacotherapy